Aphonia due to vocal cord impairment induced by carbon monoxide poisoning. Issue 2 (28th January 2014) - Koga, Shunsuke; Sadahiro, Tomohito; Ito, Shoichi; Asahina, Masato; Oda, Shigeto
<x xml:space="preserve">Abstract</x> Case We describe a case of a 22‐year‐old woman with alteration in consciousness and aphonia due to vocal cord impairment after carbon monoxide exposure. Brain magnetic resonance imaging revealed high signal intensity in bilateral globus pallidus and the pars reticulata of the substantia nigra on T2‐ and diffusion‐weighted images. Laryngeal fiberscopy showed bilateral immobilization of the vocal cords in median position during both inspiration and phonation. Although the effects of hyperbaric oxygen therapy remain ambiguous, these symptoms and magnetic resonance imaging findings subsided. Outcome Aphonia due to vocal cord impairment, as a presenting symptom of carbon monoxide poisoning, has not been previously reported. We considered the cause of aphonia was vocal cord abductor paralysis or dystonia of intralaryngeal muscles after the carbon monoxide exposure. Conclusion Even though aphonia is an unusual symptom in a patient with carbon monoxide poisoning, it must be taken into consideration.